Analysis of the Role of Agile Governance in the Development of the Smart City Concept: A Qualitative Study of the Banyumas Regency Government, Indonesia - Marfuah, Sri Rotul; Tobirin; Ali Rokhman; Muslih Faozanudin (Open Access Indonesia Journal of Social Sciences, 2024)
The smart city concept has become a new paradigm in urban development, offering innovative solutions to improve people's quality of life. Agile governance, with its flexibility and adaptability, is a promising approach in managing the complexity of smart city development. This research aims to analyze the role of agile governance in developing the smart city concept in the Banyumas Regency Government, Indonesia. This research uses a qualitative approach with a case study of the Banyumas Regency Government. Data was collected through in-depth interviews with relevant government officials, document analysis, and field observations. Data analysis was carried out using thematic coding and triangulation techniques to ensure the validity and reliability of the research results. The research results show that agile governance plays an important role in developing the smart city concept in Banyumas. Agile principles such as collaboration, iteration, and focus on customer value have been adopted in the planning, implementation, and evaluation processes of smart city programs. Agile governance allows governments to respond quickly to change, actively involve the public, and optimize the use of resources. Agile governance has proven effective in overcoming the challenges of complexity and uncertainty in smart city development. Implementing agile governance can increase the efficiency, effectiveness and sustainability of smart city programs. This research contributes to the development of agile governance theory and practice in the context of smart cities, as well as providing recommendations for other local governments who wish to adopt this approach.